Analisis faktor-faktor yang mempengaruhi pendapatan petani jagung di Kecamatan Kumpeh (studi kasus pada Desa Mekarsari) - Apri Sri Nurjanah; Hardiani Hardiani; Junaidi Junaidi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2018)
This study aims to determine the effect of age, number of family dependents, land area, and number of working hours on the income of corn farmers (case study in Mekarsari Village). The population in this study were corn farmers in Mekarsari Village which amounted to 56 respondents. The method of data collection is a questionnaire. The data analysis method used is descriptive analysis and quantitative analysis using the Ordinary Least Square (OLS) model. The results of the study show that 91.05% of corn farmers' income is influenced by age, number of family dependents, land area, and number of hours worked. Partially the age has a negative and significant effect while the land area, the number of family dependents, the number of working hours have a positive and significant effect. Simultaneously age, number of family dependents, land area, and number of hours worked significantly influence the income of corn farmers.